Sensitivity of Alpha-Methylacyl-COA Racemase (AMACR) Staining in Prostatic Adenocarcinoma - Kumar, Suresh; Bukhari, Uzma; Sikandar, Bushra; George, Aneeta; Memon, Yusra; Khan, Nehad; Bukhari, Asma (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objectives: To determine the sensitivity of Immunohistochemistry for confirmation of diagnosis of prostate adenocarcinoma in our setup. Methodology: This descriptive cross sectional study was conducted at Pathology Department of Shaukat Khanum Memorial Cancer Hospital and Research Center, in a period of six months from September 2012 to March 2013, taking a sample size of 80 biopsy proven cases of prostatic Adenocarcinoma with Non-probability purposive sampling technique. SPSS version 16 was used for data analysis. The qualitative variables like expression of AMACR were presented as frequencies and percentages. Chi square was used with a p value <0.05 taken as significant. Results: The mean ± SD age of patients was 67.81±7.25 years with a range from 51 to 85 years. The mean ± SD Gleason score of these patients was 6.99±1.52. About 51.2% (n=41) patients were of age group 61-70 years, 33.8% (n=27) were between 71-80 years, only 2.5% (n=2) were of age 81 years and above. Well-differentiated cases of prostatic adenocarcinoma were 3.8% (n=3), 52.5% (n=42) were moderately while 43.8% (n=35) were poorly differentiated. Out of all 100% (n=80) cases 91.2% (n=73) were expressed positive with AMACR staining while remaining 8.8% (n=7) were AMACR negative. Conclusion: AMACR staining is highly sensitive diagnostic tool and should be carried out in all patients who present with doubtful picture of prostatic cancer. Keywords: AMACR Staining, Prostatic Adenocarcinoma, PSA, Gleason Scoring, Immunohistochemistry.